2018
DOI: 10.1177/2325967118778507
|View full text |Cite
|
Sign up to set email alerts
|

Passive Knee Stability After Anterior Cruciate Ligament Reconstruction Using the Endobutton or ToggleLoc With ZipLoop as a Femoral Fixation Device: A Comparison of 1654 Patients From the Danish Knee Ligament Reconstruction Registry

Abstract: Background:Biomechanical studies show varying results regarding the elongation of adjustable fixation devices. This has led to growing concern over the stability of the ToggleLoc with ZipLoop used in anterior cruciate ligament (ACL) reconstruction (ACLR) in vivo.Purpose/Hypothesis:The purpose of this study was to compare passive knee stability 1 year after ACLR in patients in whom the Endobutton or ToggleLoc with ZipLoop was used for femoral graft fixation. The hypothesis was that the ToggleLoc with ZipLoop wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Four studies did not meet eligibility criteria: one could not be retrieved in full text [ 20 ], one was not written in English [ 12 ], one was conducted with several graft types [ 44 ], and presented other clinical outcomes than those included by this review [ 45 ]. Three additional studies were identified from the reference list of included studies [ 4 , 14 , 33 ]. Key characteristics for each of the included studies are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Four studies did not meet eligibility criteria: one could not be retrieved in full text [ 20 ], one was not written in English [ 12 ], one was conducted with several graft types [ 44 ], and presented other clinical outcomes than those included by this review [ 45 ]. Three additional studies were identified from the reference list of included studies [ 4 , 14 , 33 ]. Key characteristics for each of the included studies are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Three studies [ 4 , 5 , 43 ] included revision surgery in their outcome and two studies [ 28 , 34 ] reported on the number of patients undergoing revision surgery during the study period. Only the study by Asmussen et al [ 4 ] analysed the rate of revision surgery with an OR and found that ALDs had 0.51 (95% CI: 0.24–1.13) lower odds of having a revision surgery compared to FLDs. However, this was not statistically significant [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations